Entrepreneurs' social responsibilities from Islamic perspective: A study of Muslim entrepreneurs in Malaysia - Yazilmiwati Yaacob, *; Ilhaamie Abdul Ghani Azmi, (Elsevier, 2012)
The success of an entrepreneur from an Islamic perspective is not only measured in terms of material success. This is because human needs are not subjected just to the property they own, but encompasses all aspects required by the maqasid al-Shariah - namely religion, intelligence, life, honor as well as physical property. Therefore, an assessment of whether the entrepreneur succeeds or fail is based on the concept of maqasid al-Shariah. This study aims to examine the social responsibility of a Muslim entrepreneur in Malaysia in fulfilling maqasid al-Shariah aspects with regards to their responsibilities to family members, the poor as well as their responsibility towards the Muslim community by providing employment opportunities to society, doing business in accordance with Islamic law and create an economic system based on Islamic's sharia. This study will focus on the relationship between the achievement of Muslim entrepreneurs in Malaysia and their social responsibility by using Pearson's correlation test. The study found a significant relationship between the achievement of Muslim entrepreneurs in Malaysia with social responsibility undertaken by them.